The influence of occupation on overall flexibility and lower limb and lumbar range of motion - Isabel Camargo neves Sacco; Sandra Aliberti; Bergson Weber Cabral Queiroz; Denise Pripas; Isadora Kieling; Aline Aiako Kimura; Adriana Sellmer; Renan Malvestio; Marcel Sera (Universidade Federal de Santa Catarina, 2009)
The technological development in the working environment has prolonged sitting time for office employees. This prolonged sitting time may negatively influence innate physical capacities such as flexibility of the posterior chain; however, few studies have evaluated the influence of occupation on this physical capacity. This assessment might contribute to establish an early intervention approach, in parallel to the occupational activity, in order to prevent musculoskeletal dysfunctions. The aim of this study was to determine whether occupational activity influences posterior chain muscle flexibility during trunk-flexed posture and to analyze the body segments that are responsible forany flexibility changes. Twenty-four healthy women aged 18 to 55 years, who worked in cleaning and maintenance (n=13) and in offices (n=11), participated in the study. The following measurements were obtained to evaluate trunk flexion: fingertip-to-floor distance test (measuring tape), tibiotarsal angle, knee extension/flexion angle, hip angle, lumbar angle, and modified Chaffin technique (digital photogrammetry using the SAPo software). The groups were compared using the independent t-test. Women working inoffices presented the worst fingertip-to-floor test result (p=0.0518) and a lower modified Chaffin technique value (p=0.0134), whereas their tibiotarsal and hip angles were marginally greater (p=0.0609 and p=0.0713, respectively). Women who mainly work seated presented lower overall flexibility of the posterior chain muscles than women who perform occupations that require cyclic flexion of the trunk. The tibiotarsal and hip angles seem to be the body segments responsible for this reduction in flexibility.